A novel single-switch DC-DC converter using the coupled inductor with ultra-high voltage gain - Kim-Anh Nguyen; Thai Anh Au Tran; Xuan Khanh Ho; Duong Thach Pham (International Journal of Power Electronics and Drive Systems (IJPEDS), 2026)
This paper presents an extremely high step-up DC-DC converter using a quadratic topology and a coupled inductor (CI). The proposed converter (PC) utilizes a single switch, simplifying the control strategy and reducing switching losses. A passive clamp circuit recycles leakage energy, reducing voltage stress (VS) on the MOSFET and enabling the implementation of a low on-state resistance switch for higher efficiency. Additionally, the quadratic structure and passive clamp circuit contribute to higher voltage gain (VG) and better performance. The converter’s operating principles, steady-state analysis, and component selection criteria are discussed in detail. The influence of magnetizing inductance, duty cycle, and parasitic components on the VG is also investigated, along with the system’s dynamic response under input voltage and load variations to ensure stable operation. A comparative evaluation with existing converters highlights its advantages. The PC is verified through SIMPLIS simulations, where key performance metrics such as VG and switching stress are analyzed. Furthermore, a hardware prototype with a power rating of 300 W is built to confirm the theory and showcase the converter’s performance. Experimental results demonstrate high efficiency, stable operation, and substantial VG, validating the converter’s feasibility for renewable energy systems (RES).